Naturum Laponia, huvudmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2026)
Naturum Laponia is the main visitor centre (“naturum”) for the Laponia World Heritage area in Swedish Lapland, located in Stora Sjöfallet/Stuor Muorkke National Park on the Viedásnjárgga point by Lake Láŋas.
Naturum Laponia, main model
Keywords: naturum; visitor center; världsarv; world heritage site; samisk kultur; sápmi / sami culture; fjällandskap; mountain landscape; nationalpark; national park; utställning; exhibition; extremt klimat; harsh climate; cirkulär byggnad; circular building; atrium